Penegakan Hukum terhadap Kasus Pelanggaran Izin Usaha Pertambangan (IUP) pada Pertambangan Nikel - Kanda Ramandana (Program Studi Ilmu Hukum, Universitas Kuningan, 2024)
Mining is an activity that is very complex or very complicated in its implementation because not everyone can do it because it also deals with nature. If you don't pay attention to the natural ecosystem, it will damage nature, therefore mining such as mineral mining which is non-renewable energy or cannot be renewed. Permits must be prepared before carrying out mining analysis and production. The aim of the research is to analyze the regulation and law enforcement in cases of violations of mining business permits in nickel mining. The research method used in this research is descriptive-analytic with a juridical-normative type of research. The results of regulatory research are in Article 158 of Law Number 3 of 2020 concerning amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining that: